Imiona chrzestne chłopców nadane w parafii Najświętszego Serca Pana Jezusa w Częstochowie w latach 1950-1955 oraz 1980-1985 = Boys` godfather names given in the Sacred Heart of Jesus parish in Częstochowa from 1950 to 1955 and from 1980 to 1985 - Ilnicka, Daniela (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The subject of the presented study are the names given to boys in the years 1950-1955 and 1980-1985 in the parish of the Sacred Heart of Jesus in Częstochowa. The paper presents a qualitative and frequency analysis of names given for the first, second and sometimes third time. While collecting research material, the parents` forenames were also considered. To assess, whether the choice of forenames for boys was influenced by their fathers` forenames. Based on the analyses presented, one may conclude that parents are only to a small extent guided by the names they bear when naming their children.
Keywords: imię; chrzest; imię męskie; parafia pw. Najświętszego Serca Pana Jezusa w Częstochowie; name; baptism; masculine name; parish of Sacred Heart of Jesus in Częstochowa